A Study of Classroom Potential Based on Elementary School Students’ Seating Position Preferences - Satriaji, Kukuh Rizki; Santosa, Imam; Syarief, Achmad; Wibisono, Andriyanto (Revija za elementarno izobraževanje, 2025)
Previous research has shown a link between seating position and student interest in and motivation for learning. This study explores classroom potential based on seating preferences and reasons behind student choices. Teachers rarely allow students to select their own seats, despite the benefits of comfort and engagement. Conducted in 5th and 6th elementary grades, this research used a participatory approach involving students and teachers. The study found that students’ seating preferences were influenced by spatial characteristics, opportunities for social engagement, and academic motivations. Understanding these preferences can help create a more conducive learning environment, enhancing student comfort, participation, and overall academic motivation.